ANALISIS MANAGEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SMA NEGERI 6 KOTA PEMATANGSIANTAR - Kiki Immanuel Pakpahan; Debby Petra Meyana Sitorus; Benjamin Albert Simamora (JURNAL ILMIAH NUSANTARA, 2024)
The research results show that the implementation of SBM is able to increase the involvement of teachers, students and parents in the educational process. With autonomy in decision making, schools can design learning programs that are more relevant and in line with students' needs. Apart from that, SBM also encourages the development of teacher professional competence through training and collaboration. However, challenges such as lack of resources and support from the government are still obstacles in optimizing SBM. Therefore, collaborative efforts are needed between the government, schools and society to create a conducive learning environment. This research recommends increasing infrastructure support and continuous training for teaching staff to achieve better educational goals. In conclusion, SBM has great potential to improve the quality of learning, but its success is very dependent on the commitment of all stakeholders and adequate policy support. Recommendations for further research are the importance of developing the capacity of school managers in implementing SBM